(untitled) (Fiep Bulletin - online, 2013)
The Rhythmic gymnastics is a sport highly school, their movements and equipment specific to the practice are present in the daily lives of children which enables various forms of organization in the planning of physical education classes in elementary schools in particular. This study arises from the need to understand the design of the physical education teachers about their applicability and rhythmic gymnastics at school. The field research of a descriptive then presents the design of 15 physical education teachers in the city of Paraná Apucarana on rhythmic gymnastics. After signing the consent form, the questionnaire was applied in the same locations of performance. The results demonstrated that GR is known by teachers participating in the research, which had the sport in their curriculum in undergraduate institution. It was also found that their devices are recognized by them and they mostly have alternative materials for the inclusion of the sport where he teaches, but a minority of respondents said that the GR is present or has already done this in their plans classroom.